Comparison study of morphology and vascular casts between plateau‐type Tibetan sheep and low‐altitude small‐tailed Han sheep testes. (8th June 2022) - Liu, Miaomiao; Yang, Yanan; Li, Mingna; Cai, Yuan; Zhao, Shengguo; Wang, Xinrong
Abstract: We compared the differences in testicular morphology and vascular anatomy between plateau‐type Tibetan sheep and low‐altitude Small‐tailed Han sheep to explore any adaptations of Tibetan sheep to high altitudes and hypoxia factors. Testicular artery architecture specimens of plateau‐type Tibetan sheep and lowland Small‐tailed Han sheep were used to compare the physical parameters of the testis, testicular artery architecture, arterial diameter, testicular leaflets and the characteristics of epididymal head arterioles. The results showed that the weight, major axis, minor axis, overall length, caput major axis and caput minor axis in Tibetan sheep were larger than those of Small‐tailed Han sheep; however, the caput major axis of epididymal head in Tibetan sheep was smaller than that of Small‐tailed Han sheep. Compared with Small‐tailed Han sheep, the testicular knot‐like arteries of Tibetan sheep had denser spiral distribution and more small arteries, and the diameters of centripetal arteries, knot‐like arteries, centrifugal arteries and epididymal microarterioles were also thicker. The 'spindle' indentation on the surface of the microarteriole of the head of the testicular leaflets and the epididymis in plateau Tibetan sheep was relatively shallow. The results showed that the physical testicular characteristics, testicular artery construction and arteriole surface structure of Tibetan sheep were adapted for the plateau environment.